Hadith #4299 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Abu Salma al-Himsi Suliaman bin Saleem أبو سلمة الحمصي; al-Hasan bin Swar الحسن بن سوار; Auf bin Malik bin Nadlah عوف بن مالك بن نضلة - أبو الأحوص; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Isma'il bin 'Abdullah bin 'Abdullah إسماعيل بن عبد الله بن عبد الله بن أويس; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Yahya bin Jabir al-Tai'i يحيى بن جابر الطائي (Sunan Abi Dawud)
Ibn ‘Umar reported the Messenger of Allah (May peace be upon him)As saying: The Muslims will soon be besieged up to Madina so that their most distant frontier outpost will be Salah.
Grade: Sahih